Experimental Validation of the LabSOCS Detector Efficiency Simulation - Guilherme Soares Zahn; Frederico Antonio Genezini (Brazilian Journal of Radiation Sciences, 2025)
The precise knowledge of the detection efficiency for gamma ray spectrometers is often of paramount importance, and its experimental determination can be both time-consuming and challenging, especially for complex geometries and/or extensive sources. A common solution for that is the use of Monte Carlo simulations, and some companies have developed commercial solutions. In the present work, the accuracy of the efficiency values determined by Mirion Industries’ LabSOCS detection efficiency simulator was assessed by determining the activities of point sources measured under five distinct geometries, and comparing the results to the certified activity values. The results show that, while the software delivers reasonably reliable results, it tends to overestimate the efficiency, and special care may have to be taken with the precision of the geometrical measurements.